PEMAKNAAN TRADISI PETIK LAUT BAGI MASYARKAT PESISIR - Irma Juliana; Nindi Laili Safitri; Wulan Fadillah (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Indonesia has very diverse traditions and customs. The culture in Indonesia is one  of  the  historical  heritages  that  we  must  preserve  today  because  life  is  becoming more  modern,  little  by  little  eroding  the  existence  of  local  culture.  In  its  history, Indonesia  is  a  society  with  many  tribes  and  cultures  that  have  local  wisdom  that  is preserved  by  the  people.  Petik  Laut  is  one  of  the  traditions  in  Indonesia  which  is currently  still  being  carried  out  precisely  in  Puger  District,  Jember  Regency.  Puger people think that the results of the natural surroundings are a resource and the key to their well-being. Therefore, this has made some people who live in coastal areas have a tradition  that  is  carried  out  as  a  form  of  gratitude  and  thanks  because  the  natural resources they get from the sea can meet their needs. Coastal communities usually use rituals  that  have  become  a  hereditary  tradition  as  an  expression  of  gratitude.  In addition, this tradition carried out by coastal communities is also a prayer or hope that the  fish  catch  will  be  abundant  and  also  get  safety.  This  activity  is  carried  out  during Muharram or Suro. This Petik Laut tradition is an amalgamation of local wisdom and religion. In the tradition of sea cucumbers, there are prayers and recitation of the holy verses of the Koran before finally the offerings are thrown into the sea